Adhesive-free battery pole piece as well as preparation method and application thereof

Through the preparation method without adhesive, the ball mill mixes the active material, conductive agent and carbon coating agent, coats it on the current collector and calcines, solving the problem of increasing complexity and lithium ion accumulation of adhesive in the positive electrode sheet of the lithium-ion battery, and achieving high conductivity and excellent electrochemical performance.

CN119764309APending Publication Date: 2025-04-04NANCHANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411920685.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The use of binders in the existing method of preparing positive electrode sheets of lithium-ion batteries increases the process complexity and leads to lithium ions accumulation, hinders the transfer of electrons and lithium ions, and reduces electrochemical performance.

Method used

By using the preparation method without adhesive, the adhesive-free battery electrode sheet is prepared by ball milling and mixing the active material, conductive agent and carbon coating agent in a liquid environment to form a mixed slurry, coated on the current collector and dried, and then calcined in a protective atmosphere between 300°C and 700°C.

Benefits of technology

This method simplifies the process, reduces lithium ion accumulation, improves charge transfer capability, shortens ion transmission path, improves the conductivity and lithium ion diffusion coefficient of the battery pole sheet, and improves electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764309A_ABST
    Figure CN119764309A_ABST
Patent Text Reader

Abstract

The invention provides an adhesive-free battery pole piece as well as a preparation method and application thereof, and relates to the technical field of battery pole pieces. The preparation method provided by the invention comprises the following steps: ball-milling and mixing an active material, a conductive agent and a carbon coating agent in a liquid environment to prepare mixed slurry; coating a current collector with the mixed slurry, and drying to obtain a pole piece precursor; and calcining the pole piece precursor at 300-700 DEG C in a protective atmosphere to obtain the adhesive-free battery pole piece. The preparation method provided by the invention is simple to operate, low in process cost, environment-friendly, free of complex equipment and relatively high in safety, and the prepared battery pole piece does not need to use an adhesive and has excellent cycle performance and capacity performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery pole pieces, and in particular to an adhesive-free battery pole piece and a preparation method and application thereof. Background Art

[0002] In today's world, energy and environmental problems are becoming increasingly severe. Vigorously developing green electrochemical energy storage is an effective way to solve energy and environmental problems, respond to climate change, and promote green development. Lithium-ion batteries (LIBs) are an energy system with broad development prospects due to their high energy density, good cycle stability, and green environmental protection. They have been widely used in electronic devices such as laptops, mobile phones, and electric vehicles. However, the safety issues, cost issues, limited resources, and range of lithium-ion batteries have limited their further development, and these limiting factors are largely determined by the cathode materials of lithium-ion batteries.

[0003] However, in the prior art, when preparing positive electrodes for lithium-ion batteries, a binder such as PVDF is usually used as a base, mixed with active materials and conductive agents to form a traditional slurry, which is then coated on the current collector for preparation. This traditional preparation method not only increases the complexity of the process, but also the addition of non-conductive polymer binders will increase the accumulation of lithium ions, causing agglomeration, hindering the transfer of electrons and lithium ions between electrodes, increasing the electrochemical impedance, and causing the electrochemical performance of the battery to deteriorate. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide an adhesive-free battery pole piece and its preparation method and application, which do not require the use of adhesives, can reduce lithium ion accumulation, improve the charge transfer capability, and thus shorten the ion transmission path so that the battery pole piece has excellent electronic conductivity and lithium ion diffusion coefficient.

[0005] In the first aspect, the present invention provides a method for preparing an adhesive-free battery pole piece, comprising: ball-milling an active material, a conductive agent and a carbon coating agent in a liquid environment to obtain a mixed slurry; coating the mixed slurry on a current collector and drying it to obtain a pole piece precursor; and calcining the pole piece precursor at 300°C-700°C in a protective atmosphere to obtain an adhesive-free battery pole piece.

[0006] The preparation method provided by the present invention is simple to operate and has low process cost. It does not require the use of special equipment or complex equipment. It has low process cost and high safety, and is conducive to industrial large-scale production. At the same time, the prepared battery pole piece does not require the use of an adhesive, that is, a structurally stable active layer can be formed on the surface of the pole piece, which is conducive to improving the conductivity and electrochemical properties of the battery pole piece.

[0007] Optionally, the active material includes one of a lithium manganese iron phosphate positive electrode material and a silicon carbon negative electrode material.

[0008] Optionally, the conductive agent includes one of carbon nanotubes, graphene, acetylene black, and conductive carbon fibers.

[0009] Optionally, the carbon coating agent includes one of polyvinyl pyrrolidone, sodium carboxymethyl cellulose, polyvinyl alcohol, and polyethylene oxide.

[0010] Optionally, the current collector includes one of aluminum foil and graphite paper.

[0011] Optionally, the mass ratio of the active material to the conductive agent is 1:(0.2-0.6).

[0012] Optionally, the mass ratio of the active material to the carbon coating agent is 1:(0.2-0.8).

[0013] Optionally, the liquid environment is used to dissolve the carbon capping agent.

[0014] Optionally, the liquid environment includes one of deionized water, ultrapure water, and anhydrous ethanol.

[0015] Optionally, the solid-liquid ratio of the mixed slurry is 1 g: (10-15) mL.

[0016] Optionally, ball milling is performed in a liquid environment at a rotation speed of 300 rpm-400 rpm.

[0017] Optionally, ball milling is performed in a liquid environment at a ball to material ratio of 1: (1.0-1.5).

[0018] Optionally, ball milling is performed in a liquid environment for 6 h-8 h.

[0019] Optionally, when the mixed slurry is coated on the current collector, the coating thickness of the mixed slurry is 180 μm-220 μm.

[0020] Optionally, the mixed slurry is coated on at least one side of the current collector.

[0021] Optionally, the mixed slurry is coated on a partial area of ​​the side surface of the current collector.

[0022] Optionally, the mixed slurry is coated on a current collector and dried at 80°C-120°C.

[0023] Optionally, the mixed slurry is coated on a current collector and dried for 1 h to 5 h.

[0024] Optionally, in a protective atmosphere, the pole piece precursor is calcined in a first temperature zone and a second temperature zone in sequence to obtain an adhesive-free battery pole piece, and the temperature of the first temperature zone is lower than that of the second temperature zone.

[0025] Optionally, the protective atmosphere includes one of an argon atmosphere and a helium atmosphere.

[0026] Optionally, the temperature of the first temperature zone is 300°C-450°C.

[0027] Optionally, the temperature of the second temperature zone is 450°C-700°C.

[0028] Optionally, the temperature difference between the first temperature zone and the second temperature zone is 100°C-200°C.

[0029] Optionally, calcination is performed in the first temperature zone for 3 h to 5 h.

[0030] Optionally, calcination is performed in the second temperature zone for 5 h to 8 h.

[0031] Optionally, the total calcination time in the first temperature zone and the second temperature zone is 8h-13h.

[0032] Optionally, in a protective atmosphere, the pole piece precursor is heated to a temperature in a first temperature zone at a first heating rate for calcination, and is heated to a temperature in a second temperature zone at a second heating rate for calcination.

[0033] Optionally, the first heating rate and the second heating rate are independently 1°C / min-10°C / min.

[0034] In a second aspect, the present invention also provides an adhesive-free battery pole piece prepared by any of the above optional preparation methods, comprising a current collector and an active layer sintered on at least one side of the current collector, wherein the active layer comprises a conductive carbon network and an active material coated thereon.

[0035] In a third aspect, the present invention also provides an application of an adhesive-free battery electrode sheet prepared by any of the above optional preparation methods in a battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A flow chart of a method for preparing an adhesive-free battery pole piece provided by the present invention;

[0037] Figure 2 This is a scanning electron microscope image of the battery positive electrode sheet prepared in Example 1 of the present invention;

[0038] Figure 3 This is a scanning electron microscope image of the battery positive electrode sheet prepared in Example 8 of the present invention;

[0039] Figure 4This is a cycle performance diagram of the battery positive electrode sheet prepared in Example 8 of the present invention after being assembled into a button battery;

[0040] Figure 5 This is a rate performance diagram of the battery positive electrode sheet prepared in Example 8 of the present invention after being assembled into a button battery;

[0041] Figure 6 The cyclic voltammogram of the battery positive electrode sheet prepared in Example 8 of the present invention after being assembled into a button battery;

[0042] Figure 7 This is a constant current charge and discharge curve diagram of the battery positive electrode sheet prepared in Example 8 of the present invention after being assembled into a button battery. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0044] See also Figure 1 The present invention provides a method for preparing an adhesive-free battery pole piece, comprising:

[0045] S1, ball-milling the active material, the conductive agent and the carbon coating agent in a liquid environment to prepare a mixed slurry;

[0046] S2, coating the mixed slurry on a current collector and drying it to obtain a pole piece precursor;

[0047] S3. The electrode precursor is calcined at 300° C.-700° C. in a protective atmosphere to obtain an adhesive-free battery electrode.

[0048] In fact, in step S1, by ball-milling and blending the active material, the conductive agent and the carbon coating agent, it is beneficial to improve the mixing uniformity of the active material, the conductive agent and the carbon coating agent, which is beneficial to coating the mixed slurry on the current collector in step S2 to form a uniform slurry layer, and obtaining a pole piece precursor after curing, and then after calcination in step S3, the carbon coating agent can be prompted to form a carbon network to fix the active material and the conductive agent. At the same time, without using an adhesive, the energy density and cycle performance of the battery pole piece can be effectively improved.

[0049] Specifically, the active material used in step S1 includes one of lithium manganese iron phosphate positive electrode material and silicon carbon negative electrode material. In fact, the active material can use any active material commonly used in battery pole pieces, which can play a normal charge and discharge work and avoid the use of adhesives.

[0050] Specifically, the conductive agent used in step S1 includes one of carbon nanotubes, graphene, acetylene black, and conductive carbon fiber. In fact, the conductive agent can improve the conductivity of the battery pole piece by adding the conductive agent. At the same time, after the conductive agent is mixed with the carbon coating agent, it can not only form a conductive network by compounding with the conductive agent after calcination and curing, but also improve the position stability of the conductive agent.

[0051] Specifically, the carbon coating agent used in step S1 includes one of polyvinyl pyrrolidone, sodium carboxymethyl cellulose, polyvinyl alcohol, and polyethylene oxide. In fact, by using an organic carbon polymer as a carbon coating agent, the conductive agent and the active material can be fully dispersed during the mixing process, and after calcination, the carbonized conductive skeleton is formed by combining with the conductive agent.

[0052] In some embodiments, in step S1, the mass ratio of the active material to the conductive agent is 1:(2.5-4.0). In fact, by adjusting the mixing ratio of the active material to the conductive agent, the capacity performance and the conductivity of the prepared battery electrode can be balanced. In addition, the mass ratio of the active material to the carbon coating agent is 1:(0.2-0.8), which is beneficial for the carbon coating agent to uniformly coat the active material and the conductive agent after carbonization.

[0053] In some embodiments, in step S1, the liquid environment used is used to dissolve the carbon coating agent, thereby enabling the carbon coating agent to fully infiltrate the surface of the active material and the conductive agent during the ball milling process, while also improving the ball milling mixing effect of the active material and the conductive agent, thereby obtaining a mixed slurry with uniform particle size.

[0054] Specifically, the liquid environment used in step S1 includes one of deionized water, ultrapure water, and anhydrous ethanol. In fact, the liquid environment is necessary to be able to completely dissolve the carbon coating agent and to be completely removed during the drying process without introducing new impurities.

[0055] In some embodiments, the solid-liquid ratio of the mixed slurry prepared in step S1 is 1 g: (10-15) mL. In fact, by adjusting the solid-liquid ratio of the mixed slurry, the ball milling effect of the conductive agent and the active slurry during the ball milling process can be improved, and the fluidity of the mixed slurry can also be adjusted to improve the molding and drying effect of the mixed slurry on the current collector.

[0056] In some embodiments, in step S1, the active material, the conductive agent and the carbon coating agent are ball-milled and blended in a liquid environment at a speed of 300rpm-400rpm, and zirconium oxide can be used as ball milling balls, so that the active material and the conductive agent can be evenly mixed, effectively improving the surface defect degree and particle size uniformity of the active material and the conductive agent, which is beneficial to the surface wetting treatment of the carbon coating agent. Specifically, the ball-to-material ratio is 1: (1.0-1.5), and the ball milling blending is performed for 6h-8h.

[0057] Specifically, the current collector used in step S2 includes one of aluminum foil and graphite paper. In fact, after the mixed slurry is coated on the current collector, the mixed slurry can be loaded with the current collector as a matrix, so that a loose and uniform slurry layer can be formed on the surface of the current collector after drying. Specifically, the mixed slurry can be coated on one or both side walls of the current collector.

[0058] In some embodiments, when the mixed slurry is coated on the side wall of the current collector in step S2, the coating thickness of the mixed slurry is 180 μm-220 μm. Specifically, the mixed slurry can be coated on the side wall of the current collector by a coating method commonly used in the art, such as brush coating, roller coating, and dip coating. In fact, the mixed slurry can be coated on a partial area of ​​the side wall of the current collector, for example, when preparing a sheet battery, a tab position can be reserved.

[0059] In some embodiments, after the mixed slurry is coated on the side wall of the current collector in step S2, it is dried at 80°C-120°C. In fact, the liquid in the mixed slurry can be removed by the drying process, and the active layer can be preformed on the current collector. In addition, the mixed slurry can be dried in an air atmosphere or a vacuum environment, and the drying time is controlled to be 1h-5h, and it is necessary to dry to constant weight.

[0060] In fact, in step S3, by high-temperature treatment under a protective atmosphere, the carbon coating agent can be carbonized and compounded with the conductive agent to form a composite conductive network, and can be sintered with the active material to form an active layer and solidified on the surface of the current collector, thereby forming a battery pole piece with a stable structure. In addition, in the execution of step S3, the pole piece precursor is calcined in the first temperature zone and the second temperature zone in a protective atmosphere to obtain a binder-free battery pole piece, and the temperature of the first temperature zone is lower than that of the second temperature zone.

[0061] In fact, by calcining the pole piece precursor in the first temperature zone, the active layer attached to the current collector can be pre-sintered and formed, thereby effectively improving the structural stability of the active layer on the current collector. At the same time, pre-sintering can promote the decomposition and carbonization of the carbon coating agent, thereby forming a structurally stable battery pole piece during the subsequent calcination at the second temperature.

[0062] Specifically, the protective atmosphere used in step S3 includes one of an argon atmosphere and a helium atmosphere. In fact, by calcining the electrode precursor in the protective atmosphere, the carbon coating agent can be decomposed and carbonized and combined with the conductive agent to coat the active material, while avoiding oxidation of the active material and the conductive agent, thereby affecting the electrochemical performance of the battery electrode.

[0063] Specifically, when executing step S3, the temperature of the first temperature zone is 300℃-450℃, and the temperature of the second temperature zone is 450℃-700℃. In fact, when calcining in the first temperature zone and the second temperature zone, the temperature difference between the first temperature zone and the second temperature zone is 100℃-200℃, so that the pole piece precursor can be uniformly calcined and formed, thereby obtaining a battery pole piece with a stable structure. In addition, the calcination time in the first temperature zone is 3h-5h, the calcination time in the second temperature zone is 5h-8h, and the total calcination time is 8h-13h.

[0064] In some embodiments, when performing step S3, in a protective atmosphere, the pole piece precursor is heated to a first temperature at a first heating rate for calcination, and then heated to a second temperature range at a second heating rate for calcination. In fact, the first heating rate and the second heating rate are independently 1°C / min-10°C / min.

[0065] The present invention also provides a non-adhesive battery pole piece prepared by the preparation method in any of the above embodiments, which comprises a current collector and an active layer sintered on at least one side of the current collector, and the active layer comprises a conductive carbon network and an active material coated thereon. Specifically, the conductive carbon network is formed by carbonizing and sintering a conductive agent and a carbon coating agent at a high temperature.

[0066] Example 1

[0067] This embodiment 1 provides a method for preparing a positive electrode sheet of a battery without an adhesive, comprising the following steps:

[0068] S1. Add 0.5 g of lithium manganese iron phosphate LMFP55 (manganese iron ratio 5:5), 0.2 g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model MCN4301) and 0.3 g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) into 9 mL of deionized water and stir to mix. Then, use zirconium oxide balls as ball milling balls in a ball milling jar, and mill at a speed of 300 rpm for 6 h at a ball-to-material ratio of 1:1.5 to obtain a mixed slurry.

[0069] S2, using a scraper with a molding thickness of 180 μm to apply the mixed slurry on one side wall of the aluminum foil, and drying it in a forced air oven at 45° C. for 1 hour to obtain a pole piece precursor;

[0070] S3. Place the electrode precursor in the furnace of a tubular furnace, and use argon to replace the gas in the tubular furnace. Then, in an argon atmosphere, heat the electrode precursor to 350°C at a rate of 5°C / min and keep it warm for 3 hours. Then, heat it to 600°C at a rate of 5°C / min and keep it warm for 5 hours. Calcine for a total of 8 hours. After cooling to room temperature with the furnace, a binder-free battery positive electrode is obtained.

[0071] Example 2

[0072] This embodiment 2 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 1 in that in step S3, the electrode sheet precursor is heated to 350°C at a rate of 5°C / min under an argon atmosphere and calcined for 5 hours, then heated to 600°C at a rate of 5°C / min and calcined for 5 hours, and calcined for a total of 10 hours.

[0073] Example 3

[0074] This embodiment 3 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 2 in that 0.5 g of lithium manganese iron phosphate LMFP64 (manganese iron ratio 6:4) is used in step S1.

[0075] Example 4

[0076] This embodiment 4 provides a method for preparing a binder-free battery positive electrode sheet, which is different from the embodiment 2 in that 0.5 g of lithium manganese iron phosphate LMFP73 (manganese iron ratio 7:3) is used in step S1.

[0077] Example 5

[0078] This embodiment 5 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 4 in that in step S3, the electrode precursor is heated to 350°C at a rate of 3°C / min under an argon atmosphere and calcined for 5 hours, then heated to 600°C at a rate of 3°C / min and calcined for 5 hours, and then cooled to room temperature in the furnace to obtain a binder-free positive electrode sheet.

[0079] Example 6

[0080] This embodiment 6 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 5 in that the amount of deionized water added in step S1 is 5 mL.

[0081] Example 7

[0082] This embodiment 7 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 6 in that the forming thickness of the scraper in step S2 is 200 μm.

[0083] Example 8

[0084] This embodiment 8 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 7 in that in step S3, the electrode precursor is heated to 350°C at a rate of 3°C / min under an argon atmosphere and calcined for 5 hours, then heated to 550°C at a rate of 3°C / min and calcined for 5 hours, and then cooled to room temperature in the furnace to obtain a binder-free positive electrode sheet.

[0085] Example 9

[0086] This embodiment 9 provides a method for preparing a binder-free battery positive electrode sheet, which is different from the embodiment 8 in that 0.5 g of lithium manganese iron phosphate LMFP82 (manganese iron ratio 8:2) is used in step S1.

[0087] Example 10

[0088] This embodiment 10 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 8 in that in step S3, the electrode precursor is heated to 350°C at a rate of 3°C / min under an argon atmosphere and calcined for 5 hours, then heated to 500°C at a rate of 3°C / min and calcined for 5 hours, and then cooled to room temperature in the furnace to obtain a binder-free positive electrode sheet.

[0089] Embodiment 11

[0090] This embodiment 11 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 8 in that the forming thickness of the scraper in step S2 is 220 μm.

[0091] Example 12

[0092] This embodiment 12 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 8 in that 0.5 g of lithium manganese iron phosphate LMFP91 (manganese to iron ratio 9:1) is used in step S1.

[0093] Example 13

[0094] This Example 13 provides a method for preparing a binder-free battery positive electrode sheet, which is different from Example 7 in that 0.3 g of polyvinyl alcohol (purchased from Sinopharm Chemical Reagent Co., Ltd., with a molecular weight of 63800-114400) is used in step S1.

[0095] Embodiment 14

[0096] This embodiment 14 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 7 in that 0.3 g of polyethylene oxide (purchased from Sinopharm Chemical Reagent Co., Ltd.) is used in step S1.

[0097] Embodiment 15

[0098] This embodiment 15 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 4 in that 0.6g of lithium manganese iron phosphate LMFP73 (manganese-iron ratio 7:3), 0.2g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model MCN4301) and 0.2g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) are used in step S1.

[0099] Example 16

[0100] This embodiment 16 provides a method for preparing a binder-free battery positive electrode sheet, which is different from embodiment 4 in that 0.6g of lithium manganese iron phosphate LMFP73 (manganese-iron ratio 7:3), 0.15g of multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model MCN4301) and 0.25g of polyvinyl pyrrolidone (purchased from Sinopharm Chemical Reagent Co., Ltd.) are used in step S1.

[0101] Comparative Example 1

[0102] This comparative example 1 provides a method for preparing a positive electrode sheet, comprising the following steps:

[0103] D1, 0.5g lithium manganese iron phosphate LMFP73 (manganese iron ratio 7:3), 0.23g multi-walled carbon nanotubes (purchased from Shenzhen Feimo Technology Co., Ltd., model MCN4301) were added into 5mL deionized water and stirred and mixed, and then zirconium oxide balls were used as ball milling balls in a ball milling jar, and the mixed slurry was prepared at a ball-to-material ratio of 1:1.5 at a speed of 300 rpm for 6 hours;

[0104] D2. Dry the mixed slurry in a blast oven at 60°C for 12 hours to obtain a precursor powder, place the precursor powder in the furnace of a tube furnace, heat it to 350°C at a rate of 3°C / min under an argon atmosphere and calcine it for 3 hours, then heat it to 550°C at a rate of 3°C / min and calcine it for 5 hours, calcine it for a total of 8 hours, and cool it to room temperature with the furnace to obtain a composite powder;

[0105] D3. 0.9 g of composite powder, 0.1 g of PVDF and 1.4 mL of NMP were mixed and homogenized to obtain composite slurry. The composite slurry was coated on one side wall of the aluminum foil using a scraper with a molding thickness of 180 μm, and dried in a forced air oven at 80° C. for 12 h to obtain a positive electrode sheet.

[0106] Performance Testing

[0107] The positive electrode sheets of the batteries prepared in Example 1 and Example 8 were characterized by scanning electron microscopy, and the results were as follows: Figure 2 and Figure 3 shown.

[0108] The positive electrode sheets prepared in Example 1, Example 2, Example 4 to Example 11, Example 15, and Comparative Example 1 were assembled into button cells in a glove box using 1 mol / L lithium hexafluorophosphate (the solvent is a mixture of dimethyl carbonate, ethylene carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1) as an electrolyte, a lithium sheet as a battery negative electrode sheet, and celgard 2500 as a separator. The discharge specific capacity of the button cells was measured at a current density of 0.1C, and the results are shown in Table 1 below.

[0109] The button cell corresponding to Example 8 was tested using a Xinwei electrochemical test system (CT-4008T) in the voltage range of 2.7V-4.3V (vs. Li + / Li) for electrochemical performance testing, and its cycle performance is as follows Figure 4 As shown, the rate performance is Figure 5 The cyclic voltammetric performance is shown in Figure 6 As shown, the constant current charge and discharge performance is as follows Figure 7 shown.

[0110] Table 1 Discharge specific capacity at 0.1C current density

[0111] Discharge specific capacity (mAh / g) Discharge specific capacity (mAh / g) Example 1 142.3 Example 8 156 Example 2 135.8 Example 9 149.5 Example 4 149.2 Example 10 140 Example 5 148.1 Embodiment 11 148.1 Example 6 151.3 Embodiment 15 132.9 Example 7 149.7 Comparative Example 1 120

[0112] from Figure 2 and Figure 3 It can be seen that the active materials on the surface of the positive electrode are all nanorods with a width of 200nm-300nm and a length of 300nm-500nm. Since no adhesive is used, ion accumulation can be effectively avoided, so that the particles on the surface of the positive electrode can be evenly distributed, and no particle aggregation is observed in the SEM image. In addition, it can be seen that the carbon nanotubes are evenly dispersed around the LMFP particles, thereby constructing an interconnected conductive network, which can not only enhance the diffusion capacity of lithium ions, but also improve the rate performance of the positive electrode material.

[0113] from Figure 4 It can be seen that the battery discharge capacity is as high as 156mAh / g at 0.1C, and after 500 cycles at 1C, the capacity retention rate is 96.02%, and the coulombic efficiency is close to 100%, highlighting the good cycle stability. Figure 5 It can be seen that at 0.1, 0.2, 0.5, 1, 2, 3 and 5C rates, the highest discharge specific capacities are 148.8, 146.9, 142.1, 136.3, 128.9, 122.5 and 110.9 mAh / g, respectively, further demonstrating the excellent high rate performance and charge and discharge stability. Figure 6 It can be seen that at high rates, the contribution of capacitance is dominant, and lithium ions can be stored quickly, so it has better rate performance. Figure 7 It can be seen that the charge and discharge platform remains well maintained with slight polarization phenomenon, indicating that the material has a stable structure and therefore has good cycle performance.

[0114] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A method for preparing an adhesive-free battery pole piece, characterized in that: include: The active material, the conductive agent and the carbon coating agent are mixed by ball milling in a liquid environment to prepare a mixed slurry; The mixed slurry is coated on a current collector and dried to obtain a pole piece precursor; the pole piece precursor is calcined at 300-700° C. in a protective atmosphere to obtain an adhesive-free battery pole piece.

2. The preparation method according to claim 1, characterized in that: The active material includes one of lithium manganese iron phosphate positive electrode material and silicon carbon negative electrode material; and / or, the conductive agent includes one of carbon nanotubes, graphene, acetylene black, and conductive carbon fiber; and / or, the carbon coating agent includes one of polyvinyl pyrrolidone, sodium carboxymethyl cellulose, polyvinyl alcohol, and polyethylene oxide; and / or, the current collector includes one of aluminum foil and graphite paper.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the active material to the conductive agent is 1:(0.2-0.6); and / or, the mass ratio of the active material to the carbon coating agent is 1:(0.2-0.8); and / or, the liquid environment is used to dissolve the carbon coating agent; and / or, the liquid environment includes one of deionized water, ultrapure water, and anhydrous ethanol.

4. The preparation method according to claim 1, characterized in that: The solid-liquid ratio of the mixed slurry is 1g:(10-15)mL; and / or, ball milling is performed in a liquid environment at a rotation speed of 300rpm-400rpm; and / or, ball milling is performed in a liquid environment at a ball-to-material ratio of 1:(1.0-1.5); and / or, ball milling is performed in a liquid environment for 6h-8h.

5. The preparation method according to claim 1, characterized in that: When the mixed slurry is coated on the current collector, the coating thickness of the mixed slurry is 180μm-220μm; and / or, the mixed slurry is coated on at least one side of the current collector; and / or, the mixed slurry is coated on a partial area of ​​the side of the current collector; and / or, the mixed slurry is coated on the current collector and dried at 80℃-120℃; and / or, the mixed slurry is coated on the current collector and dried for 1h-5h.

6. The preparation method according to claim 1, characterized in that: In a protective atmosphere, the pole piece precursor is calcined in a first temperature zone and a second temperature zone in sequence to obtain an adhesive-free battery pole piece; the temperature of the first temperature zone is lower than that of the second temperature zone.

7. The preparation method according to claim 6, characterized in that: The protective atmosphere includes one of an argon atmosphere and a helium atmosphere; and / or, the temperature of the first temperature zone is 300°C-450°C; and / or, the temperature of the second temperature zone is 450°C-700°C; and / or, the temperature difference between the first temperature zone and the second temperature zone is 100°C-200°C; and / or, calcination in the first temperature zone is 3h-5h; and / or, calcination in the second temperature zone is 5h-8h; and / or, the total calcination time in the first temperature zone and the second temperature zone is 8h-13h.

8. The preparation method according to claim 6, characterized in that: In a protective atmosphere, the pole piece precursor is heated to a temperature in a first temperature zone at a first heating rate for calcination, and is heated to a temperature in a second temperature zone at a second heating rate for calcination; the first heating rate and the second heating rate are independently 1°C / min-10°C / min.

9. An adhesive-free battery electrode sheet prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The invention comprises a current collector and an active layer sintered on at least one side of the current collector, wherein the active layer comprises a conductive carbon network and an active material coated thereon.

10. Use of the adhesive-free battery pole sheet prepared by the preparation method according to any one of claims 1 to 8 in a battery.

Citation Information

Patent Citations

  • Fluorinion-doped lithium iron phosphate material and preparation methods thereof

    CN102024951A

  • Secondary battery

    CN115528296A

  • Binder-free positive electrode for zinc ion battery and preparation method of binder-free positive electrode

    CN117497683A

  • Binder-free silicon-based negative electrode for lithium ion battery and preparation method of binder-free silicon-based negative electrode

    CN117497704A